Viral antibody studies in pancreatic disease. Issue 11 (November 1975) - Capner, P; Lendrum, R; Jeffries, D J; Walker, G
Abstract : Viral studies were performed on sera from 54 patients with recent acute pancreatitis, 10 with recurrent acute pancreatitis, seven with chronic pancreatitis, and 10 with pancreatic carcinoma, and on sera from 81 age- and sex-matched controls. In 29 of the acute pancreatitis patients from whom paired sera were obtained no convincing evidence of recent viral infection was found. A higher incidence of raised antibody titres against Coxsackie B3 and B4 was observed in the group of acute pancreatitis patients compared with their controls. The possible signficance of these observations and their relationship to the aetiology of the pancreatitis and to other immunological findings are discussed.